Surirella subrotunda sp. nov. and Surirella parahelvetica sp. nov., two new diatom (Bacillariophyta) species from Lake Prespa, Macedonia - Cvetkoska, Aleksandra; Levkov, Zlatko; Hamilton, Paul B. (Phytotaxa, 2014)
The genus Surirella is highly diverse and many taxa are reported as endemic, especially from ancient lakes and tropical continental regions. In ancient Lake Ohrid, 25 different Surirella species have been identified by different authors, five are considered to be endemic for the lake. In contrast, research on its sister Lake Prespa has been less rigorous and data for recent and fossil species of Surirella is very sparse. The number of Surirella taxa reported from Lake Prespa is 11; only one is considered an endemic for both lakes, Ohrid and Prespa. In this study, taxa from the genus Surirella were observed in a number of recent and fossil samples from Lake Prespa. Two taxa possess unique characters that distinguish them from known species. Their formal descriptions, based on detailed LM and SEM observations, are presented here. Surirella subrotunda sp. nov. is differentiated from other similar species by its valve outline, size, and shape of median area; it has been observed only in fossil diatom samples from core Co1215 recovered from Lake Prespa. Surirella parahelvetica sp. nov. is distinguished by its size, valve outline, number of alar canals and stria density.